Pemetaan Kondisi dan Potensi BMT: Kemitraan dalam Rangka Memperluas Pasar & Jangkauan Pelayanan Bank Syariah kepada Usaha Mikro - Ali Sakti (AL-MUZARA'AH, 2013)
The limitations faced by Islamic Bank in terms of range, scope, service network and low competency of human resources serving micro and small enterprises have made linkage and partnership with Islamic microfinance institutions such as BMT become very important. On the other hand, weaknesses of BMT industry, such as the availability of information about the profile and performance of BMT, need to be enhanced by conducting surveys in the area that become the centers of BMT operation. Therefore, this study attempts to survey the condition and potential of BMT in three provinces in Java, namely West Java, Central Java and East Java. Survey on major variables such as asset volume and BMT financial performance shows very high variation. The findings also show that fundamental reform of governance is highly required, especially with respect to regulation and supervision of the BMT industry. In the short term, improvements can be made by optimizing the role of the Association of BMT and BMT Agencies. In general, based on various indicators, the performance of BMT in Central Java is better than those in East Java and West Java